Efficient distributed feedback dye laser in silk fibroin films - Silva, R. R.D. [UNESP]; Dominguez, C.Tolentino; Santos, M.V. Dos [UNESP]; Melo, L.S.A. De; Barbosa-Silva, R.; Cavicchioli, M. [UNESP]; Christovam, L. M. [UNESP]; Ribeiro, S. J.L. [UNESP]; Araújo, C. B.D.; Gomes, A. S.L. (IEEE, 2012)
We observed longitudinal single-mode operation in a distributed feedback dye laser consisting of silk fibroin films doped with Rhodamine 6G dye and infiltrated with silica or silver nanoparticles. © OSA 2012.